Analyse statistique des pluies journalières extrêmes à partir d un seuil dans le Bénin subéquatorial - HOUNVOU, Sourou Ferdinand; GUEDJE, KOSSI FRANÇOIS; KOUGBEAGBEDE, Hilaire; ADECHINAN, A. Joseph; HOUNGNINOU, BODOU ETIENNE (My University, 2019)
West Africa's high climate variability has severe socioeconomic impacts on people's lives. There is a need to better understand its physical mechanisms to improve the prediction and prediction of floods and droughts in this region of the world. The analysis of extreme rainfall above a threshold is made for this purpose in subequatorial Benin. Daily rainfall data are collected seventeen (17) stations in southern Benin. The results show thresholds ranging between 17.4973 mm and 37.9033 mm on the one hand and a growth in the annual number of rainfall heights greater than a threshold after the resumption of rain in the 1980s or early 1990s on the different study stations. With a significantly negative shape parameter, the Pareto generalized law allows to adjust well the daily rains superior to only one.
Keywords: Climate variability; statistical; analysis; threshold; Pareto law; daily; rainfall; Benin subequatorial